Fermentation of Musa paradisiaca Peels to Produce Citric Acid - Mariel Monrroy; Lineth Rueda; Anaís L. Aparicio; José Renán García (Journal of Chemistry)
Among organic acids, citric acid (CA) features the highest production volume and the greatest economic potential. The steadily increasing demand for CA necessitates the improvement and diversification of the corresponding production techniques via the incorporation of more environmentally friendly and less costly processes such as the bioconversion of agroindustrial by-products. Musa paradisiaca, known as plantain, is a food product of global importance; however, the related by-products are scarcely utilized. Herein, we investigate CA production from M. paradisiaca peels via fermentation with Aspergillus niger. Compositional analysis shows that the above peels contain 623 g·kg−1 total carbohydrates, 374 g·kg−1 starch, and 91 g·kg−1 protein and therefore are rather rich in carbon, with other elements contained in substantial amounts corresponding to K (28 g·kg−1), N (10 g·kg−1), Fe (39 mg·kg−1), Na (71 mg·kg−1), Zn (16 mg·kg−1), and Cu (18 mg·kg−1). Evaluation of solid-substrate fermentation conditions (pH and inoculum loading) reveals that CA production is maximized (29 g·kg−1) at 10% consistency, 30°C, pH 1.4, and inoculum loading = 20 mg, demonstrating that pH is the most important parameter determining fermentation efficiency. As a result, M. paradisiaca peels are concluded to be a suitable substrate for CA biosynthesis via fermentation with A. niger under optimal nutritional conditions.